MODIFIED CYCLODEXTRIN-BASED THERMOSENSITIVE IN SITU GEL FOR VORICONAZOLE OCULAR DELIVERY AGAINST FUNGAL KERATITIS - SAMPATHI, SUNITHA; MADDUKURI, SRAVYA; RAMAVATH, RAMDAS; DODOALA, SUJATHA; KUCHANA, VIJAYA (International Journal of Applied Pharmaceutics, 2024)
Objective: Fungal keratitis is a severe corneal infection. The present study aims to design and formulate an inclusion complex of Voriconazole-Sulfobutyl ether-beta-cyclodextrin (V-SBECD) loaded thermosensitive in-situ gel to improve solubility, therapy efficacy, durability and reduce the dose-related side effect. Methods: Poloxamer 407, a thermosensitive polymer along with hydroxypropyl methylcellulose (HPMC E 15), were used as gelling agents; the formulations with poloxamer (16% w/v) and HPMC E15 (1 and 1.5 % w/v) led to a consistent in-situ gel at 37 °C. The formulations were evaluated for drug content, pH, gelation temperature, viscosity, sterility test, antifungal studies, and cell lines studies. Results: The molar ratio of the drug to SBECD (1:3), showing 42-fold increase in solubility, was chosen to prepare the inclusion complexes using the lyophilization method. The stability constant was found to be 721-m. ATIR peaks, DSC thermograms and NMR spectra indicate the inclusion behavior of Voriconazole and SBECD. In vitro and ex-vivo studies demonstrated that optimized formulation sustained the drug release for over 12 h. Cellular cytotoxicity on Human corneal epithelial cells showed that V-SBECD formulations do not cause corneal epithelial damage after 24 h. In-situ gel and marketed formulation have shown a markable reduction in the growth of the Aspergillus Niger. The optimized SBECD-loaded in-situ gel formulation (F10) did not vary significantly in pH, drug content, viscosity, and % cumulative drug release, signifying stable formulations when tested at 4, 25, and 40 °C. Conclusion: The research findings envisaged V-SBECD in-situ gel formulation as a concrete strategy to treat severe fungal keratitis.